The Veterinary Profession in a Changing Environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Veterinary Profession in a Changing Environment Proceedings of the Commonwealth Veterinary Association and Kenya Veterinary Association joint conference for Eastern, Central and Southern Africa, held in April 1999 in Nairobi, Kenya. Edited by W O O